A 1-year study on the maintenance of gingival health by a dentifrice containing a zinc salt and non-anionic antimicrobial agent - Svatun, B; Saxton, C A; Rölla, G; van der Ouderaa, F (Journal of clinical periodontology, 1989)
An experimental dentifrice containing zinc citrate and Triclosan was used by student nurses for 12 months without supervision, while a corresponding group used a control dentifrice. Dental flossing was not permitted during the first 6 months. Gingival health achieved in a pre-experimental period, during which oral hygiene instruction was given, was maintained by users of the experimental dentifrice for 12 months but not by users of the control dentifrice. About 1/3 of the control group used floss daily during the 2nd 6 months and significantly improved their gingival health to a level comparable to that of the experimental group. Flossing brought no extra benefit for the latter group. In the control group, approximal regions were less healthy than buccal or lingual sites. The gingival health of these sites improved significantly with daily flossing. The experimental dentifrice maintained gingival health in all sites irrespective of the use of floss. The study has confirmed that oral health can be maintained by the use of the experimental dentifrice for at least 12 months in a habitual toothbrushing regime, and that the dentifrice would be as effective and simpler than relying on the combination of brushing and regular flossing.